2009
DOI: 10.1111/j.1476-4431.2009.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

The cell‐based model of coagulation

Abstract: Objective -To review the current model describing coagulation processes, including the critical contributions of cells. Data Sources -Original research articles, scientific reviews, and textbooks. Data Synthesis -Normal hemostasis is vital for prevention of blood loss, but controls are necessary to limit coagulation to the site of injury. The previous cascade model of blood coagulation, although refined and updated over the last few decades, is flawed as a description of how hemostasis occurs in vivo. The rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
142
1
32

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(183 citation statements)
references
References 22 publications
1
142
1
32
Order By: Relevance
“…ref. [92][93][94][95][96] Although most modern models of coagulation incorporate the role of cells, 1,87,102,103 we shall concentrate here on the strippeddown terminal elements of the extrinsic (and common) pathway, where thrombin plays a crucial role in initiating the polymerisation of fibrinogen. These terminal processes, that are our focus here, are shown in Fig.…”
Section: Relationship Between Chronic Inflammation and Hypercoagulabimentioning
confidence: 99%
See 1 more Smart Citation
“…ref. [92][93][94][95][96] Although most modern models of coagulation incorporate the role of cells, 1,87,102,103 we shall concentrate here on the strippeddown terminal elements of the extrinsic (and common) pathway, where thrombin plays a crucial role in initiating the polymerisation of fibrinogen. These terminal processes, that are our focus here, are shown in Fig.…”
Section: Relationship Between Chronic Inflammation and Hypercoagulabimentioning
confidence: 99%
“…in ref. [86][87][88], but both converge on terminal steps in which prothrombin is converted Fig. 1 Some risk factors, associated with hypercoagulability.…”
Section: Relationship Between Chronic Inflammation and Hypercoagulabimentioning
confidence: 99%
“…В последние годы развитие клеточной модели сверты-вания крови in vivo позволило определить, что TF является единственным инициатором образования тромбина, попада-ющим в кровоток при повреждении эндотелия кровеносных сосудов под воздействием травмы, провоспалительных цито-кинов, эндотоксина, адреналина, гипоксии или значитель-ной кровопотери [34,47]. ТF входит в число интегральных мембраносвязанных гликопротеинов и экспрессируется на клетках крови и эндотелия, а также взаимодействует с присутствующим в крови фактором VII с образованием комплекса «ТF -FVIIa» (так называемая фаза инициации свертывания крови).…”
unclassified
“…Coagulation is assessed globally, from the first phase of clot formation to the final lysis of the clot (McMichael and Smith 2011). Furthermore, the viscoelastic technique is a whole blood assessment that considers the role of plasmatic haemostatic components as well as platelets and cellular surfaces, and better reflects the cell-based model of coagulation (Smith 2009). A recent study has identified hypercoagulability by means of non-activated TEG in 7 dogs affected by renal failure and in 11 dogs with severe proteinuria (Donahue et al 2011).…”
mentioning
confidence: 99%